KETERSEDIAAN UANG SEBAGAI PEMODERASI GAYA HIDUP KONSUMTIF TERHADAP PERILAKU KONSUMTIF MINUMAN KOPI KEKINIAN PADA GENERASI MILENI - Krismi Budi Sienatra; Nurul Ulfa Khadizah (KOLONI, 2022)
Consumption of coffee, especially contemporary coffee, has now become a habit carried out by young people, especially those called the millennial generation. Coffee consumption is a lifestyle for them and they do not hesitate to set aside a budget to buy coffee. This study examines the consumptive lifestyle on consumptive behavior with the availability of money as a moderating variable that tests whether it strengthens or weakens the relationship. The study was conducted in the city of Balikpapan with samples in this study being individuals aged 19-30 years who consumed coffee in 1 week at least 3 times with a final selection of 390 people. The study was tested with multiple regression to test the independent variable, namely consumptive lifestyle, and the dependent variable, namely consumptive behavior with the moderating variable of money availability. The results showed that the consumptive lifestyle had a significant effect on consumptive behavior and the availability of money moderated strengthening the relationship between consumptive lifestyles and consumptive behavior. Kata kunci: consumptive lifestyle, consumptive behavior, availability of money